Literature Review: Mitigasi Resiko dan Prosedur Penyelamatan pada Sistem Perkreditan Rakyat - Sutrisno Sutrisno; Ludia Panggalo; Muhammad Asir; Muhammad Yusuf; Pandu Adi Cakranegara (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Distribution of People's Business Credit is influenced by government regulations for the Bank and is expected to reduce the level of credit risk in Non-Performing Loans. So that many cause problems in the form of bad credit. Banks that provide KUR services are required to carry out risk management. The financing risk faced by Islamic banking is one of the risks that needs to be managed properly due to internal errors. The method in this research is a literature study by reviewing some of the results of previous research which originates from national and international articles. The research results were analyzed and used as material for discussion to determine answers to problems regarding the relationship between risk mitigation and rescue procedures in the people's credit system. All ideas from each study provide information about the methodologically desirable theory of the study being analyzed. The results of the literature review show that proper handling is needed by loan managers such as banks or cooperatives in overcoming various problems in the procurement of people's credit, namely KUR. One that is done is risk mitigation and rescue procedures to avoid losses to the manager. Keywords: Risk Mitigation, Rescue Procedures, People's Credit, Banking.